On a Concept of Black Politics. Issue 173 (1st December 2022) - Forjwuor, Bernard
Abstract: How do we define Black politics conceptually? What is the conceptual jurisdiction from which it is framed as distinct from other political concepts? The concept of Black politics, I argue, operates as a force of refusal of the inevitability of liberalism as the 'end of history.' It repudiates what liberal politics routinely represents as pacific, universal, rational and inclusive to the field of politics. The concept of Black politics, then, is an anamorphic signifier that destabilises dominant conceptions of liberal politics as inevitable. I make two arguments in this article: first, that liberalism is an anaemic singularity that excludes the imperial and racial assemblages in which it is implicated, and second, that the concept of Black politics is anamorphic in so far as it creates the possibility for emancipation that transcends this liberal obligation in its imperial and racial assemblages.